2012
DOI: 10.1007/s11033-012-1641-9
|View full text |Cite
|
Sign up to set email alerts
|

The TT genotype of methylenetetrahydrofolate reductase 677C>T polymorphism increases the susceptibility to pediatric ischemic stroke: meta-analysis of the 822 cases and 1,552 controls

Abstract: The 677C>T polymorphism within methylenetetrahydrofolate reductase (MTHFR) gene is related to an elevated level of homocysteine. Thus it may be considered as a genetic risk factor in ischemic stroke. Apparently studies of this type of polymorphism in childhood stroke have shown conflicting results. We performed meta-analysis of all the data that are available in relation with MTHFR polymorphism and the risk of ischemic stroke in children. We searched PubMed (last search dated December 2010) using “MTHFR polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…20 A meta-analysis of 14 studies, conducted by SareckaHujar et al showed that TT genotype of MTHFR gene was more common in pediatric stroke patient than controls (OR 1.57, 95% CI 1.02-2.41). 21 Another meta-analysis, which included 19 case-control studies involving 2223 cases and 2936 controls also suggested that MTHFR C677T polymorphism was significantly associated with increased risk of ischemic stroke. 14 The mechanism of association between MTHFR polymorphism and ischemic stroke is not clear; however, studies have shown that a single base pair replacement of Cytosine nucleotide with Thymine at 677 nucleotide position of MTHFR gene influences enzyme thermolability, its decreased activity and, in turn, the elevated level of Hcy, an endothelial toxin especially in the presence of low folate levels 22 and in effect to elevated risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…20 A meta-analysis of 14 studies, conducted by SareckaHujar et al showed that TT genotype of MTHFR gene was more common in pediatric stroke patient than controls (OR 1.57, 95% CI 1.02-2.41). 21 Another meta-analysis, which included 19 case-control studies involving 2223 cases and 2936 controls also suggested that MTHFR C677T polymorphism was significantly associated with increased risk of ischemic stroke. 14 The mechanism of association between MTHFR polymorphism and ischemic stroke is not clear; however, studies have shown that a single base pair replacement of Cytosine nucleotide with Thymine at 677 nucleotide position of MTHFR gene influences enzyme thermolability, its decreased activity and, in turn, the elevated level of Hcy, an endothelial toxin especially in the presence of low folate levels 22 and in effect to elevated risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis of available data [11] confirmed the association between the carrier state of the 677T allele in the MTHFR gene and AIS in children. However, the role of another common MTHFR polymorphism, 1298A>C in paediatric stroke, is still uncertain.…”
Section: Introductionmentioning
confidence: 74%
“…In turn, in children with AIS from Lebanon, 677C>T polymorphism within the MTHFR gene was found to be present in the patients who suffered from recurrent stroke, as well as those who had multiple risk factors for AIS [67]. Previously, the T allele carrier-state of 677C>T polymorphism in the MTHFR gene was proved to increase the risk of AIS in children [68], in contrast to another common 1298A>C polymorphism in the MTHFR gene [69]. The polymorphic 677TT variant of the MTHFR gene was previously linked to a higher level of homocysteine, one of the biochemical risk factors for cerebroand cardiovascular diseases, both in children and adults.…”
Section: Genetic Polymorphismsmentioning
confidence: 99%